2020
DOI: 10.1038/s41598-020-77182-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value and potential association of Rab1A and FoxM1 aberrant expression in colorectal cancer

Abstract: Colorectal carcinoma (CRC) is one of the most common malignancies with a dismal 5-year survival rate. Our recent study indicated that Rab1A expression was closely related to GLI1 expression. A previous study shows that aberrant overexpression of GLI1 promotes colorectal cancer metastasis via FoxM1 overexpression. However, the potential correlation between Rab1A and FoxM1 in CRC remains elusive. Immunohistochemistry was performed to investigate the association of the expression of Rab1A and FoxM1 and to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A previous study has reported that Rab1A overexpression caused a poor prognosis in CRC 9 , 30 , 31 , GC 32 , and intrahepatic cholangiocarcinoma 19 . The Rab1A positive group had a worse prognosis than the negative group in GC patients.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A previous study has reported that Rab1A overexpression caused a poor prognosis in CRC 9 , 30 , 31 , GC 32 , and intrahepatic cholangiocarcinoma 19 . The Rab1A positive group had a worse prognosis than the negative group in GC patients.…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies indicated Rab1A, an oncogene, is aberrantly elevated in various cancers. Furthermore, Rab1A overexpression led to poor prognoses, including lung cancer 16 , liver cancer 17 , and colorectal cancer 30 . A previous study reported that Rab1A and IL4Ra expression is highly associated with lung cancer tissues 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has reported that Rab1A overexpression led to a poor prognosis in CRC 9,30,31 , GC 32 and intrahepatic cholangiocarcinoma 19 . Our results suggest that Rab1A positive group had a worse prognosis compared with the negative group in GC patient.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, Rab1A overexpression led to poor prognosis, such as lung cancer 16 , liver cancer 17 , colorectal cancer 30 . Previous study reported that the expression of Rab1A and IL4Ra is highly correlated in lung cancer tissues 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, RAB1A emerges as a promising candidate for targeted intervention in colorectal cancer, with its interaction with FoxM1 warranting deeper exploration. (43),(44),(45)…”
Section: Introductionmentioning
confidence: 99%